Perforation of the pulmonary artery with Swan-Ganz catheters: diagnosis and surgical management. - Kelly, T F (1981)
Swan-Ganz catheters have become a very valuable and frequently used method of monitoring hemodynamics in sick patients. Although the incidence of complications is very low, more reports are beginning to appear. One of the more serious complications is the rupture of the pulmonary artery. This report concerns three patients who had a rupture of the pulmonary artery who survived, including one of almost fatal exanguination. A literature review of all cases of pulmonary artery rupture is presented. Fifty-three per cent (8/15) were fatal. Emphasis is placed on the prevention of this by using the guidelines. Discussion also covers possible contributing causes and treatment. A high index of suspicion is necessary whenever a patient with the catheter has hemoptysis or unexplained cardiac or respiratory changes.